Religious Understanding among Highschool Students in Bandung: Analysis on Attitude and Perspective toward Issues of Islamic Law, Religious Freedom, Tolerance, and Pancasila - Rusliana, Iu; Kahmad, Dadang (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2020)
This study aims to reveal the religious understanding of millennials (focus on ‘Rohis’ in senior high school) in Bandung. The authors will try to analyze how the views and attitudes of millennials towards several issues consisting of Islamic law, religious freedom, tolerance, and Pancasila. The research methodology used is a case study approach. Also, data is collected through in-depth interviews, focus group discussions, and observations. This study found that the majority of millennials in Bandung have inclusive and moderate understanding. The majority of them reject various ideas and discourses such as the Islamic state, intolerance, violence in the name of religion, and to replace Pancasila as the principle of the nation. Besides, they also rejected several radical groups that wanted to replace the basis of the nation. However, some students approve the existence of hard-line groups and they agree to replace Pancasila as the basis of the Indonesian nation